PERSEPSI SISWA SMK NEGERI 1 LALAN TERHADAO PROSPEK BEKERJA DI SEKTOR PERTANIAN - Mahfiroh, Ummi; Anang, Rahidin (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2025)
ABSTRACTThis study aims to examine the perceptions of students at SMK Negeri 1 Lalan regarding career prospects in the agricultural sector and to identify the factors influencing their interest. The research was conducted from February to March 2025 using a case study approach. Informants were selected purposively, consisting of 12th-grade agriculture students who ranked among the top 10 academically. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using descriptive qualitative methods, including data condensation, data display, and conclusion drawing. The results indicate that students have a generally positive yet realistic perception of agriculture. They acknowledge its strategic role in supporting food security and national economic development and see promising opportunities if the sector is managed with modern, technology-based approaches. However, they are also aware of challenges such as price fluctuations, limited access to capital, and low interest among their peers. Student interest is influenced by internal factors (personal motivation, early experiences, intention to continue family farming, entrepreneurial orientation, and positive views on agriculture’s flexibility and profitability) and external factors (family support, social environment, technological advancement, and structural barriers such as limited land and access to finance). ABSTRACTPenelitian ini bertujuan untuk mengkaji persepsi siswa SMK Negeri 1 Lalan terhadap prospek bekerja di sektor pertanian serta mengidentifikasi faktor-faktor yang memengaruhi minat mereka. Penelitian dilakukan pada Februari–Maret 2025 dengan pendekatan studi kasus. Informan terdiri dari siswa kelas XII jurusan pertanian yang masuk dalam 10 besar akademik, dipilih melalui teknik purposive sampling. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi, kemudian dianalisis secara deskriptif kualitatif melalui tahapan kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa siswa memiliki persepsi positif namun realistis terhadap sektor pertanian. Mereka memahami peran strategis pertanian dalam ketahanan pangan dan pembangunan ekonomi, serta melihat peluang apabila dikelola secara modern dan berbasis teknologi. Meski demikian, siswa juga menyadari tantangan seperti fluktuasi harga, keterbatasan modal, dan rendahnya minat generasi muda. Minat mereka dipengaruhi oleh faktor internal (motivasi pribadi, pengalaman masa kecil, keinginan meneruskan usaha keluarga, orientasi kewirausahaan, dan pandangan positif terhadap pertanian) serta faktor eksternal (dukungan keluarga, pengaruh lingkungan sosial, kemajuan teknologi, dan hambatan struktural seperti keterbatasan lahan dan akses modal).